Study guides

☆☆

Q: What is the answer for 3 3x-6 -3 1 plus 4x?

Write your answer...

Submit

Still have questions?

Related questions

8563

5x + 3 - 4 + 4x = 9x -1

x2 + 4x + 3 = (x + 1)(x + 3)

(4x - 3)(4x - 1)

5x + 3 - 4 + 4x = 9x -1

-17

x2 + 4x + 3 =(x + 3) (x + 1)

4x + 4x + 3 = 8x + 3 which cannot be factorised.

-26

(4x - 3)(x - 1)

3 minus 3 times 6 plus 2 =

4x^2 + 3

x2 + 4x + 3 = 0 (x + 1)(x + 3) = 0 x ∈ {-3, -1}

(4x + 3)(4x + 3) (4x + 3)2

If 4x + 7 = 3... then x must equal -1

-1 = 3 + 4x take 3 away from both sides: -4 = 4x divide both sides by 4 -1 = x

5 1/3 = 4x/3 + 4 1 1/3 = 4x/3 4/3 = 4x/3 x = 1

4x+8x+3 = 12x+3

4x + 1 = 4Subtract 1 from both sides:4x = 3Divide both sides by 4x = 3/4 or .75

4x plus 3 plus 2x is equivalent to expression 6x plus 3.

1

(4x + 1)(2x + 3)

4x-3+6x+3 4x+6x=10x -3+3=0 10x is the answer!

2x + 4x + 3 = 6x + 3

True.3x^4 + 4x^3 - 3x^4 + 5x + 1= 4x^3 + 5x + 1